The Impact of Leadership Style, Work Environment, and Organizational Culture on the Performance of Sub-district Employees in Tasikmalaya Regency - Fitri Ajeng Sari (Jurnal Inovasi Bisnis dan Kewirausahaan, 2026)
This research aims to analyze the influence of leadership style, work environment, and organizational culture on job performance. The study was conducted among district employees in Tasikmalaya Regency. Sampling was carried out using a proportional random sampling technique, involving 100 respondents across 39 districts. Data were collected via a Likert-scale questionnaire and analyzed using path analysis with SPSS version 26. The descriptive results indicate that work environment, organizational culture, and job performance fall into the "good" category, while leadership style is categorized as "very good." Furthermore, the study finds that leadership style, work environment, and organizational culture, both partially and simultaneously, have a positive and significant effect on performance.